Eastern Mosquitofish, Gambusia holbrooki, for Control of Mosquito Larvae - Eric Jon Cassiano; Jeffrey E. Hill; Quenton Tuckett; Craig A. Watson (EDIS)
Using native animal species, particularly fish, to reduce mosquito populations is popular in multiple states including Florida. This 5-page fact sheet written by Eric Jon Cassiano, Jeffrey Hill, Quenton Tuckett, and Craig Watson and published by the Program in Fisheries and Aquatic Sciences within the UF/IFAS School of Forest Resources explains how to use eastern mosquitofish to control mosquitoes. It also discusses other native fish species that may reduce mosquito populations. http://edis.ifas.ufl.edu/fa202